Association Between Indian and U.S. Stock Markets : Volatility Spillover Effect Using GARCH Models - Savadatti, Pushpa M. (Indian Journal of Research in Capital Markets, 2018)
This paper explored the possibilities of volatility spillover between the Indian stock market and the U.S. stock market. For this purpose, BSE Sensex (India) and Dow Jones (USA) stock market indices were selected, and the analysis was based on the weekly stock returns for a period of 1997 to 2018 using generalized auto regressive conditional heteroscedasticity (GARCH) technique along with Granger - causality test, Augmented Dicky Fuller test, and Phillips - Peron test. The Granger - causality test indicated the existence of unidirectional causation flowing from the American stock market to the Indian stock market. The GARCH (1,1) model was estimated to study the volatility spillover effect between the two markets and the results displayed the existence of volatility spillover from the American stock market (DOW) to the Indian stock market (BSE Sensex) as the spillover coefficient was positive and statistically significant. It was further observed that the volatility in the BSE stock market was highly persistent. The analysis is of great importance to domestic investors, policy makers, companies, and regulatory authorities for effective decision making in the competitive world.